Phytoseiid mites (Acari: Phytoseiidae) from Argentina, with description of a new species - Guanilo, Alberto Daniel; de Moraes, Gilberto José; Toledo, Silvana; Knapp, Markus (Zootaxa, 2008)
This paper reports the mites of the family Phytoseiidae known from Argentina. It is based mostly on a survey conducted in the northern region of that country as well as on published information. Twenty-two species were found in that survey, ten of which are new records from that country, including a new species here described as Neoseiulus argentinus Guanilo & Moraes n. sp.. Measurements of all species collected and a taxonomic key to separate the species known to date from Argentina are provided. All together 47 species are reported from Argentina.